2013
DOI: 10.1002/jnr.23332
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of thoracic motor and sensory neurons and spinal nerve roots in canine degenerative myelopathy, a potential disease model of amyotrophic lateral sclerosis

Abstract: Canine Degenerative Myelopathy (DM) is a progressive adult-onset multisystem degenerative disease with many features in common with amyotrophic lateral sclerosis (ALS). As with some forms of ALS, DM is associated with mutations in superoxide dismutase 1 (SOD1). Clinical signs include general proprioceptive ataxia and spastic upper motor neuron paresis in pelvic limbs, which progress to flaccid tetraplegia and dysphagia. The purpose of this study was to characterize DM as a potential disease model for ALS. We p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 43 publications
(88 reference statements)
5
30
0
Order By: Relevance
“…Sensory involvement may thus play an important role in CDM disease progression. The loss of thoracic sensory root axons and the evidence of degeneration in DRG neurons are consistent with the report of CDM-associated sensory nerve pathology (Griffiths and Duncan, 1975), although the degenerative changes that Morgan et al (2014) observed in the DRG neurons were more profound than the mild central chromatolysis previously reported. Although clinical signs of CDM and ALS are primarily associated with motor dysfunction, sensory deficits are also known to occur as part of the clinical spectrum of both diseases (Averill, 1973;Dyck et al, 1975;Mulder et al, 1983;Andersen et al, 1995Andersen et al, , 1996Isaacs et al, 2007;Pugdahl et al, 2007;Coates and Wininger, 2010).…”
Section: Sensory Involvementsupporting
confidence: 86%
See 3 more Smart Citations
“…Sensory involvement may thus play an important role in CDM disease progression. The loss of thoracic sensory root axons and the evidence of degeneration in DRG neurons are consistent with the report of CDM-associated sensory nerve pathology (Griffiths and Duncan, 1975), although the degenerative changes that Morgan et al (2014) observed in the DRG neurons were more profound than the mild central chromatolysis previously reported. Although clinical signs of CDM and ALS are primarily associated with motor dysfunction, sensory deficits are also known to occur as part of the clinical spectrum of both diseases (Averill, 1973;Dyck et al, 1975;Mulder et al, 1983;Andersen et al, 1995Andersen et al, , 1996Isaacs et al, 2007;Pugdahl et al, 2007;Coates and Wininger, 2010).…”
Section: Sensory Involvementsupporting
confidence: 86%
“…A histopathological examination revealed the loss of large myelinated nerve fibers as well as clusters of presumptive regenerating fibers in common peroneal nerves (Morgan et al, 2014). Degeneration of intramuscular nerve branches, as evidenced by myelin ovoids and nerve fiber loss, has been observed in all affected Boxers at the later disease stage, consistent with a dyingback polyneuropathy.…”
Section: Peripheral Neuropathymentioning
confidence: 96%
See 2 more Smart Citations
“…A presumptive clinical diagnosis is made by ruling out potential causes of compressive myelopathy; however, confirmation requires histopathological examination of the spinal cord (16). The pathological features of DM are similar to the pathological features of ALS (17)(18)(19)(20)(21)(22). DM has been confirmed in over 24 breeds (16,23) and presumptively reported in another nine breeds (16).…”
Section: Significancementioning
confidence: 99%